Preparation method and application of NiFe-LDH / BiVO4 nanocomposite material

Through NiFe-LDH/BiVO4 nanocomposite as the photoanode, the problems of unfavorable kinetics of water oxidation reactions and high cost of precious metal catalysts in photoelectrochemical cells are solved, and the efficient synthesis of FDCA at room temperature is achieved, with high efficiency and high selectivity and Low cost features.

CN115613057BActive Publication Date: 2024-12-27SHAOXING BAILISHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211255884.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-13
Publication Date
2024-12-27
Estimated Expiration
2042-10-13

AI Technical Summary

Technical Problem

The kinetics of water oxidation reactions in existing photoelectrochemical cells are unfavorable, the product O2 has no significant value, and the use of precious metal catalysts is high and easy to poison, the reaction selectivity is poor, and there are many by-products, which affects the yield of FDCA.

Method used

NiFe-LDH/BiVO4 nanocomposite material is used as the photoanode, and porous and loose BiVO4 film is prepared by electrodeposition-calcination and hydrothermal method, and NiFe-LDH is loaded to build a PEC system, using oxygen in water as an oxidant, driven by solar light The synthesis of FDCA is achieved with 5-HMF, and the reaction is carried out at room temperature without adding oxygen. It has high efficiency, high selectivity and high yield.

Benefits of technology

It has achieved efficient and highly selective catalysis at low electrolytic potentials, the Faraday efficiency can reach 100%, the yield of FDCA also reaches 100%, the oxidation performance of the catalyst is greatly improved, the process is simple, the cost is low, and the reaction is green and mild.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115613057B_ABST
    Figure CN115613057B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a NiFe-LDH / BiVO4 nanocomposite material, wherein a BiVO4 nanoporous film is first grown on a conductive glass FTO by an electrodeposition method, and then the film is used as a substrate material, and a BiVO4 nanocomposite material loaded with NiFe-LDH is prepared by a hydrothermal method. The nanocomposite material can be directly used as a photoanode for photoelectrochemical oxidation of 5-hydroxymethylfurfural to synthesize 2,5-furandicarboxylic acid. Compared with the competitive reaction of water oxidation, the composite electrode exhibits excellent reaction selectivity, and the Faraday efficiency can reach 100%; by adjusting the concentration of the reaction medium 2,2,6,6-tetramethylpiperidine-nitrogen-oxide, the electrolysis potential can be reduced, the energy conversion efficiency can be improved, and a high yield of FDCA can be achieved at the same time. The method of the present invention does not require the participation of oxygen, the reaction conditions are mild and controllable, and the yield and Faraday efficiency are extremely high, and the requirements for the reaction device are also low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano functional materials and biomass photoelectrocatalysis, and specifically relates to a NiFe-LDH / BiVO 4 The invention relates to a method for preparing a nanocomposite material and applying it to the photo-electrochemical oxidation synthesis of biomass derivatives. Background Art

[0002] As humans exploit and utilize fossil energy, energy crises and environmental pollution become increasingly severe, we must develop new clean energy sources. Photoelectrochemical cells (PECs) can directly utilize photogenerated electron-hole pairs generated on the surface of semiconductors to produce fuels, just as nature produces oxygen through photosynthesis. In a typical PEC, fuel is generated by a reduction reaction on the cathode that consumes photoexcited electrons. For example, water is reduced to hydrogen and carbon dioxide is reduced to carbon-based fuels such as methanol and methane. However, water oxidation is not a kinetically favorable reaction, and its product O 2 There is no significant value either. Therefore, identifying an anode reaction with more favorable kinetics and capable of producing value-added chemicals will help improve the overall efficiency and utilization of PEC. Organic photoelectric synthesis has attracted increasing attention due to its advantages such as low cost, high efficiency, cleanliness, and low energy consumption, and can combine organic selective synthesis with energy development (hydrogen production). The holes generated on the surface of the photoanode are transferred to the anode chamber for selective organic synthesis, and the generated electrons are transferred to the cathode chamber through an external circuit for hydrogen production. Herein, the present invention selects the biomass derivative 5-hydroxymethylfurfural (5-HMF) as a reaction substrate for selective photoelectric oxidation to synthesize 2,5-furandicarboxylic acid (FDCA), an important organic synthesis intermediate, which is listed as one of the 12 biomass platform molecules by the U.S. Department of Energy. It has a similar conjugated isoelectronic structure to terephthalic acid and is considered to be a potential substitute for it for the manufacture of polyesters, polyamides and polyurethanes.

[0003] In the existing technology, Au, Pt, Ru and other precious metals are mainly used as catalysts to selectively oxidize HMF to synthesize FDCA. The catalyst cost is high and it is easy to be poisoned and inactivated. On the other hand, the reaction needs to be introduced with oxygen as an oxidant, which not only requires the addition of ventilation equipment, but also has poor reaction selectivity and many by-products, which affects the yield of FDCA. In view of this, the present invention uses semiconductor materials as photoanodes to construct a PEC system, uses oxygen in water as an oxidant, uses sunlight as an energy source, and applies a lower bias voltage to achieve the selective oxidation of 5-HMF at room temperature and normal pressure to synthesize FDCA. The reaction conditions are green and mild, and have a high reaction efficiency and yield of FDCA. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a NiFe-LDH / BiVO4 Preparation method and application of nanocomposite materials. Firstly, porous BiVO was prepared on FTO substrate by electrodeposition-calcination method. 4 The film has a particle size of 150-300nm; and NiFe-LDH is loaded on it by hydrothermal method, and its size is 50-300nm. 4 It can be directly used as a photoelectrode material for the TEMPO-mediated photoelectrochemical oxidation of 5-HMF to synthesize FDCA under sunlight-driven conditions. The reaction does not require the addition of oxygen and can be carried out at room temperature and pressure. It has low requirements for the reaction device, is easy to operate, and has the characteristics of high selectivity, high yield, and high efficiency. 4 It has a typical type II heterojunction structure, which can effectively separate photogenerated holes and electrons and prolong the carrier lifetime. At the same time, the effective reduction of the valence band improves the surface oxidation kinetics of the catalyst, enabling a highly efficient and highly selective catalytic process at a lower electrolysis potential (0.6Vvs.RHE): the Faraday efficiency can reach ~100%; the yield of FDCA is ~100%; and the oxidation performance of the catalyst is greatly improved.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A NiFe-LDH / BiVO 4 The method for preparing the nanocomposite material comprises the following steps:

[0007] (1) dissolving potassium iodide and bismuth nitrate in deionized water and adjusting the pH value to 1.6 to 1.8; separately weighing p-benzoquinone and dissolving it in anhydrous ethanol; mixing the two solutions and stirring them evenly to obtain an electrolyte for electrodeposition;

[0008] (2) using a typical three-electrode system for constant potential electrodeposition, with FTO as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode; applying a voltage of -0.1 V in the electrolyte of step (1) for deposition, and after completion, taking out the FTO, rinsing it, and blowing it dry to obtain a BiOI precursor;

[0009] (3) The dimethyl sulfoxide solution of vanadium acetylacetonate is uniformly dripped onto the surface of the BiOI precursor prepared in step (2), and then the sample is placed in a muffle furnace for calcination, and the sample is taken out after cooling to room temperature in the furnace, and then immersed in a NaOH solution, taken out, rinsed with deionized water, and dried to obtain BiVO 4 film;

[0010] (4) Urea, ammonium fluoride, nickel nitrate hexahydrate, and ferric nitrate nonahydrate were dissolved in deionized water in a molar ratio of 125:50:25:3, stirred evenly, and then transferred to a hydrothermal reactor. The BiVO obtained in step (3) was 4 The film was added to the inner tank and placed in an oven for hydrothermal reaction. After the reaction, the surface was rinsed with anhydrous ethanol and vacuum dried to obtain NiFe-LDH / BiVO 4 Nanocomposite materials.

[0011] In step (1), the molar ratio of potassium iodide to bismuth nitrate is 10:1; and the mass ratio of p-benzoquinone to potassium iodide is 1:6.5.

[0012] In step (3), 0.1062 g of vanadyl acetylacetonate is weighed and dissolved in 1 mL of dimethyl sulfoxide to prepare a dimethyl sulfoxide solution of vanadyl acetylacetonate; the amount of the dimethyl sulfoxide solution of vanadyl acetylacetonate used is 100 μL.

[0013] In step (3), the sample is heated to 450° C. at a heating rate of 2° C. / min in a muffle furnace and calcined for 2 hours; the concentration of the NaOH solution is 1 mol / L.

[0014] In step (4), BiVO 4 The conductive surface of the film is placed obliquely upward in the inner tank; the hydrothermal reaction temperature is 120°C and the reaction time is 6 hours.

[0015] BiVO 4 The particle size is 150-300 nm, and the size of NiFe-LDH grown thereon is 50-300 nm.

[0016] A NiFe-LDH / BiVO 4 Application of nanocomposites, NiFe-LDH / BiVO 4 The nanocomposite was directly used as a photoanode for photoelectrochemical oxidation of 5-hydroxymethylfurfural to synthesize 2,5-furandicarboxylic acid, including the following steps: NiFe-LDH / BiVO 4 The nanocomposite material is used as a photoanode, a platinum sheet is used as a cathode, and Ag / AgCl is used as a reference electrode. A boric acid buffer is added to the cathode chamber, and a boric acid buffer containing 2,2,6,6-tetramethylpiperidine-nitrogen-oxide and 5-hydroxymethylfurfural is added to the anode chamber. A xenon lamp equipped with an AM1.5G filter is used to simulate sunlight and irradiate the back of the photoanode. A bias voltage is applied to catalyze the oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid.

[0017] An equal volume of buffer was added to the cathode chamber and the anode chamber. The borate buffer in the anode chamber contained 3-5 mg / ml 2,2,6,6-tetramethylpiperidine-N-oxide and 5 mM 5-hydroxymethylfurfural.

[0018] The anode and cathode chambers were separated by Nafion 117 proton exchange membrane; the light intensity on the back of the photoanode was 100 mW / cm 2 ; Applied bias ≤1.0V vs.RHE, passed charge ≤55C.

[0019] The beneficial effects of the present invention are:

[0020] The present invention provides a NiFe-LDH / BiVO 4 The preparation method of the nanocomposite material has the advantages of simple process, short time consumption and low cost. The raw materials of the nanocomposite material are abundant and inexpensive, which can meet the cost requirements of industrial applications. The introduction of NiFe-LDH reduces the valence band position and improves the hole oxidation ability, so that the potential of the reaction is effectively reduced. On this basis, a TEMPO-mediated PEC system is constructed, which does not require the participation of oxygen and can achieve efficient and selective conversion of 5-HMF to synthesize high-value-added FDCA under the drive of sunlight. The reaction is green and mild, with extremely high Faradaic efficiency and yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 BiVO obtained in Example 1 4 Scanning electron microscope (SEM) images of the films at different magnifications.

[0022] Figure 2 NiFe-LDH / BiVO obtained in Example 1 4 SEM of composite materials.

[0023] Figure 3 BiVO obtained in Example 1 4 Thin films and NiFe-LDH / BiVO 4 X-ray diffraction (XRD) patterns of the composites.

[0024] Figure 4 The BiVO obtained in Example 1 4 Thin films and NiFe-LDH / BiVO 4 UV-visible diffuse reflectance spectrum of -1 composite material.

[0025] Figure 5 In Example 2, BiVO 4 Linear sweep voltammetry (LSV) curves of the thin film photoelectrode under (a) the presence and absence of sunlight irradiation and (b) the switching response at different potentials.

[0026] Figure 6 In Example 2, NiFe-LDH / BiVO 4LSV of the composite photoelectrode under (a) the presence and absence of sunlight irradiation and (b) the switching response at different potentials.

[0027] Figure 7 In Example 2, BiVO 4 (a) Constant potential 0.7 V electrolysis curve and charge amount and (b) yield of oxidation products of photoelectrooxidation of 5-HMF by thin film as photoanode; (c) constant potential 1.0 V electrolysis curve and charge amount and (d) yield of oxidation products.

[0028] Figure 8 This is the reaction pathway diagram for the synthesis of FDCA by photoelectrochemical oxidation of 5-HMF.

[0029] Fig. 9 In Example 2, NiFe-LDH / BiVO 4 Composite material as photoanode photoelectrooxidation of 5-HMF (a) constant potential 0.7V electrolysis curve and charge amount and (b) curve of oxidation product variation with charge amount; (c) constant potential 1.0V electrolysis curve and charge amount and (d) conversion rate, selectivity and FDCA yield of 5-HMF.

[0030] Fig.10 This is a graph showing the change in oxidation products over time of the photoelectrochemical oxidation of 5-HMF to FDCA in Example 3. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:

[0032] Example 1: BiVO 4 Thin films and NiFe-LDH / BiVO 4 Preparation of composite materials

[0033] Take 3.32g of potassium iodide and dissolve it in 50mL of deionized water and stir it evenly. Adjust the pH to 1.7 with concentrated nitric acid, then add 0.97g of bismuth nitrate pentahydrate and stir it thoroughly to dissolve (solution A). Then dissolve 0.5126g of p-benzoquinone in 20mL of ethanol and stir it thoroughly to dissolve (solution B). Pour solution B into solution A and mix well to obtain a deposition solution.

[0034] The washed and dried FTO was used as the working electrode, Ag / AgCl as the reference electrode, and the platinum sheet as the counter electrode. The sample was deposited at -0.1 V vs. Ag / AgCl for 5 minutes. After the reaction, the sample was taken out and rinsed with anhydrous ethanol and dried with nitrogen to obtain a BiOI precursor sample.

[0035] Weigh 0.1062g of vanadium acetylacetonate and ultrasonically dissolve it in 1mL of dimethyl sulfoxide solvent. Take 100 microliters of the solution and evenly drop it on the surface of the BiOI precursor sample. Place the sample in a muffle furnace and set the program temperature to: increase the temperature to 450℃ at a rate of 2℃ / min. Keep it warm for 2 hours and then cool it down to room temperature naturally. Then immerse it in 1M NaOH solution for 30 minutes to remove the unreacted substances remaining on the surface. Take it out, rinse it with deionized water, and dry it to obtain BiVO 4 film.

[0036] Weigh 0.5 mmol of nickel nitrate hexahydrate, 0.06 mmol of ferric nitrate nonahydrate, 2.5 mmol of urea, and 1 mmol of ammonium fluoride and dissolve them in 80 mL of deionized water. Stir evenly and transfer to the inner tank of the hydrothermal reactor. Add BiVO 4 Thin film materials (BiVO 4 The film was placed in the inner container with the conductive surface facing upwards and then placed in an oven for hydrothermal reaction at 120°C for 6 hours. After the reaction, the sample was taken out, rinsed with ethanol, and then vacuum dried for 6 hours to obtain NiFe-LDH / BiVO 4 .

[0037] Figure 1 and Figure 2 The BiVO obtained in Example 1 are 4 Thin films and NiFe-LDH / BiVO 4 SEM images of the composite material at different magnifications. It can be clearly seen that the porous BiVO 4 The film is loaded with NiFe-LDH nanoparticles and nanosheets. 4 The particle size of the film is 150-300 nm, and the particle size of the NiFe-LDH grown thereon is 50-300 nm.

[0038] Figure 3 The BiVO obtained in Example 1 4 Thin films and NiFe-LDH / BiVO 4 X-ray diffraction (XRD) diagram of the composite material. As can be seen from the figure, BiVO 4 Thin films and NiFe-LDH / BiVO 4 The composite materials all contain monoclinic scheelite phase BiVO 4 (JCPDS no.83-1698). The derivative peaks at 2θ values ​​of 19.02°, 28.93°, 30.52°, 42.47° and 78.26° correspond to monoclinic scheelite BiVO 4In addition, the derivative peak at 2θ value of 11.53° corresponds to the (003) crystal plane of NiFe-LDH (JCPDS no.51-0463).

[0039] Figure 4 (a) is the BiVO obtained in Example 1 4 Thin films and NiFe-LDH / BiVO 4 UV-Vis diffuse reflectance spectrum of the composite material. Based on the absorption spectrum, BiVO 4 The absorption of the film starts at about 510nm and increases with decreasing wavelength. Fig. 9 (b) The calculated optical band gap is about 2.51 eV. Thanks to the narrower band gap of NiFe-LDH, NiFe-LDH / BiVO 4 The absorption of the composite material is broadened to 590nm, and the absorption in the ultraviolet region is slightly higher than that of BiVO 4 The optical band gap of the film is reduced to 2.23eV, which is beneficial to the capture of sunlight and improves the ability of light absorption.

[0040] Example 2: NiFe-LDH / BiVO 4 Application of nanocomposites to synthesize FDCA by photoelectrochemical oxidation of 5-HMF driven by sunlight

[0041] Construction of a PEC system for 5-HMF photoelectrooxidation and testing of BiVO 4 Thin films and NiFe-LDH / BiVO 4 Catalytic performance of the composite material as a photoanode: In an H-type electrolyzer, the BiVO prepared in Example 1 4 Thin film or NiFe-LDH / BiVO 4 The composite material is the photoanode, the platinum sheet is the cathode, and the Ag / AgCl is the reference electrode. A 0.5M boric acid buffer is added to the cathode chamber, and an equal volume of boric acid buffer containing 2,2,6,6-tetramethylpiperidine-nitrogen-oxide and 5-hydroxymethylfurfural is added to the anode chamber (the boric acid buffer contains 3mg / ml 2,2,6,6-tetramethylpiperidine-nitrogen-oxide (TEMPO) and 5mM 5-HMF), wherein TEMPO is used as a reaction medium, and the anode and cathode chambers are separated by a Nafion 117 proton exchange membrane. A xenon lamp (300W) equipped with an AM1.5G filter is used to simulate sunlight and irradiate the back of the photoanode, and the light intensity is controlled at 100mW / cm 2 All measured voltages E (Ag / AgCl) are converted to the potential E relative to the reversible hydrogen electrode (RHE) (RHE) :E (RHE)=E (Ag / AgCl) +0.1976+0.0592*pH.

[0042] The photoelectric test was carried out by linear sweep voltammetry (LSV) at a scan rate of 10 mV / s. Figure 5 (a) is the BiVO 4 Linear sweep voltammetry (LSV) curves of the thin film as a photoelectrode with and without sunlight irradiation: As the voltage is swept from 0.2V to 1.4V, the dark current is very small, almost 0, and the current rises slightly at 1.4V, about 0.43mA / cm 2 ; Under light conditions, the current rises sharply, and the photocurrent is 4.0mA / cm at 1.4V 2 In comparison, NiFe-LDH / BiVO 4 The dark current of the composite material is similar and almost zero, such as Figure 6 As shown in (a), the photocurrent has been greatly improved, and the photocurrent is 5.8mA / cm at 1.4V. 2 .

[0043] The light-dark current response (It curve) was tested by the constant potential method, such as Figure 5 As shown in (b), BiVO 4 The film exhibits a stable switching effect, with a photoresponse of 0.65 mA / cm at 0.7 V. 2 , 1.0V is the light response of 2.16mA / cm 2 ;like Figure 6 (b) shows NiFe-LDH / BiVO 4 The composite material also exhibits a stable switching effect, but the photocurrent is significantly improved, which is 3.13 mA / cm at 0.7 V and 1.0 V respectively. 2 , the photoresponse is 5.33mA / cm 2 .

[0044] Finally, electrolysis was performed at a fixed potential: BiVO 4 When the film is a photoanode, bias voltages of 0.7 V and 1.0 V are applied respectively to catalyze the oxidation of 5-HMF to generate FDCA. After a certain reaction time, the content of FDCA is determined by high performance liquid chromatography, the yield is calculated, and the Faraday efficiency is calculated by the amount of electricity. Figure 7 As shown in a, after 7 hours of electrolysis at 0.7 V, the amount of electricity passed was only 17C, the Faraday efficiency was 2.5%, the FDCA yield was only 1.7%, the intermediate product 5-formyl-2-furancarboxylic acid (FFCA) yield was 57.27%, and the 2,5-diformylfuran (DFF) yield was 10.96. Figure 7 (b)); the applied bias voltage was increased to 1.0V, and the amount of electricity passed through the electrolysis for 6 hours was 48C ( Figure 7(c)), the Faradaic efficiency is 93.9%; the FDCA yield is increased to 94.5% ( Figure 7 (d)).

[0045] The detection of intermediate products shows that the photoelectrochemical oxidation of 5-HMF to FDCA is a six-electron process ( Figure 8 ), the hydroxyl group is first oxidized to an aldehyde group to obtain 2,5-diformylfuran (DFF); then an aldehyde group on DFF is oxidized to a carboxyl group to obtain 5-formyl-2-furancarboxylic acid (FFCA); finally, another aldehyde group is also oxidized to a carboxyl group to obtain FDCA.

[0046] NiFe-LDH / BiVO 4 When the composite material is a photoanode, bias voltages of 0.7V and 1.0V are applied respectively to catalyze the oxidation of 5-HMF to generate FDCA. After a certain reaction time, the content of FDCA is determined by high performance liquid chromatography, the yield is calculated, and the Faraday efficiency is calculated by the amount of electricity. After 7 hours of electrolysis at 0.7V, the amount of electricity passed is 54C, and the Faraday efficiency is 97% ( Fig. 9 (a)), FDCA yield 100% ( Fig. 9 (b)); the applied bias voltage was increased to 1.0V, and the electrolysis lasted for 6 hours with a charge of 55C ( Fig. 9 (c)), the Faradaic efficiency was 97%; the conversion of 5-HMF, FDCA yield and selectivity all reached ∼100% ( Fig. 9 (d)).

[0047] Example 3: Effect of TEMPO concentration on the synthesis of FDCA by photoelectrooxidation of 5-HMF

[0048] The NiFe-LDH / BiVO prepared in Example 1 4 The composite material is a photoanode, and a PEC system for photoelectrooxidation of 5-HMF as in Example 2 is constructed. In an H-type electrolyzer, a 0.5 M boric acid buffer is added to the cathode chamber, and an equal volume of boric acid buffer containing 5 mg / ml TEMPO and 5 mM 5-HMF is added to the anode chamber. The anode and cathode chambers are separated by a Nafion117 proton exchange membrane. A xenon lamp (300 W) equipped with an AM1.5G filter is used to simulate sunlight and irradiate the back of the photoanode. The light intensity is controlled at 100 mW / cm 2 . Apply 0.6V for constant potential electrolysis. After 5 hours, the amount of electricity can reach ~55C, the Faradaic efficiency is ~100%, the conversion rate is ~100%, and the FDCA yield is ~100% ( Fig.10 ).

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of a NiFe-LDH / BiVO4 nanocomposite material, characterized in that: NiFe-LDH / BiVO4 nanocomposite was directly used as a photoanode for photoelectrochemical oxidation of 5-hydroxymethylfurfural to synthesize 2,5-furandicarboxylic acid, including the following: In an H-type electrolytic cell, NiFe-LDH / BiVO4 nanocomposite material was used as a photoanode, a platinum sheet was used as a cathode, and Ag / AgCl was used as a reference electrode. A boric acid buffer was added to the cathode chamber, and a boric acid buffer containing 2,2,6,6-tetramethylpiperidine-nitrogen-oxide and 5-hydroxymethylfurfural was added to the anode chamber. A xenon lamp equipped with an AM1.5G filter was used to simulate sunlight and irradiate the back of the photoanode. A bias voltage was applied to catalyze the oxidation of 5-hydroxymethylfurfural to produce 2,5-furandicarboxylic acid. The method for preparing the NiFe-LDH / BiVO4 nanocomposite material comprises the following steps: (1) Dissolve potassium iodide and bismuth nitrate in deionized water and adjust the pH value to 1.6-1.8; weigh p-benzoquinone and dissolve it in anhydrous ethanol; mix the two solutions and stir them evenly to obtain an electrolyte for electrodeposition; (2) using a typical three-electrode system for constant potential electrodeposition, with FTO as the working electrode, Ag / AgCl as the reference electrode, and platinum as the counter electrode; applying a voltage of -0.1 V in the electrolyte of step (1) for deposition, and after the deposition, taking out the FTO, rinsing it and blowing it dry, thereby obtaining a BiOI precursor; (3) uniformly dripping a dimethyl sulfoxide solution of vanadium acetylacetonate onto the surface of the BiOI precursor prepared in step (2), then placing the sample in a muffle furnace for calcination, cooling it to room temperature, taking it out, and then immersing it in a NaOH solution, taking it out, rinsing it with deionized water, and drying it to obtain a BiVO4 film; (4) Urea, ammonium fluoride, nickel nitrate hexahydrate and ferric nitrate nonahydrate are dissolved in deionized water in a molar ratio of 125:50:25:3, stirred evenly and transferred to the inner tank of a hydrothermal reactor, the BiVO4 film obtained in step (3) is added to the inner tank, and placed in an oven for hydrothermal reaction; after completion, the surface is rinsed with anhydrous ethanol, and vacuum dried to obtain a NiFe-LDH / BiVO4 nanocomposite material.

2. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: In step (1), the molar ratio of potassium iodide to bismuth nitrate is 10:1; and the mass ratio of p-benzoquinone to potassium iodide is 1:6.

5.

3. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: In step (3), 0.1062 g of vanadyl acetylacetonate is weighed and dissolved in 1 mL of dimethyl sulfoxide to prepare a dimethyl sulfoxide solution of vanadyl acetylacetonate; the amount of the dimethyl sulfoxide solution of vanadyl acetylacetonate used is 100 μL.

4. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: In step (3), the sample is heated to 450°C in a muffle furnace at a heating rate of 2°C / min and calcined for 2 hours; the concentration of the NaOH solution is 1 mol / L.

5. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: In step (4), the BiVO4 film is placed in the inner container with the conductive surface facing upward; the hydrothermal reaction temperature is 120°C and the reaction time is 6 hours.

6. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: The BiVO4 particles are 150~300 nm in size, and the NiFe-LDH grown on them is 50~300 nm in size.

7. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: An equal volume of buffer was added to the cathode chamber and the anode chamber. The borate buffer in the anode chamber contained 3-5 mg / ml 2,2,6,6-tetramethylpiperidine-N-oxide and 5 mM 5-hydroxymethylfurfural.

8. The use of a NiFe-LDH / BiVO4 nanocomposite material according to claim 1, characterized in that: The anode and cathode chambers were separated by Nafion 117 proton exchange membrane; the light intensity on the back of the photoanode was 100 mW / cm 2 ; Applied bias ≤1.0Vvs. RHE, Pass charge ≤55 C.